GENERAL PRINCIPLES OF GERIATRIC REHABILITATION - Cringuta Paraschiv; Irina Esanu; Rodica Ghiuru; Cristina Maria Gavrilescu (Romanian Society of Oral Rehabilitation, 2015)
This paper is an overview of the geriatric rehabilitation, focusing on the particularities that differentiate it from the recovery of younger adults. Elderly patients present an increased prevalence of progressive disabling chronic conditions requiring rehabilitation and they are also more exposed to acute disability events due to a chronic disease. Rehabilitation is an essential component of geriatric care and therapy and it can make a critical difference in the life quality of elderly people, even though the process is much more difficult and the progress may be slower than in younger adults. The goal of the geriatric rehabilitation is the recovery and the development of personal independence and the ability to do as many as possible daily living activities. Special programs must be designed for the older people involving an interdisciplinary approach because geriatric rehabilitation must be adapted to 1) the physiological age related decline including sensory impairments, mental status deficiency, depression or dementia, physical inactivity, lack of endurance, impaired balance 2) multiple coexisting chronic diseases and 3) constrained finances, 4) lack of social and sometimes family support.